2021
DOI: 10.1002/cpdd.1018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of the α2C‐Adrenoreceptor Antagonist BAY 1193397 in Healthy Male Subjects

Abstract: The α 2C -adrenoreceptor antagonist BAY 1193397 is in development for the oral treatment of diabetic foot ulcers. Safety, tolerability, and pharmacokinetics of BAY 1193397 were investigated in 3 randomized, single-center phase 1 studies in healthy male subjects: a first-in-human study (single oral doses of 0.5-50 mg), a relative bioavailability and food effect study (single doses of 1 and 10 mg), and a multiple-dose escalation study (using 2 and 5 mg twice daily and 10 and 20 mg once daily for 9 consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Particularly, interest in inhibiting the biological activity of vascular α 2C -adrenoceptors (which play a role as thermo-effectors) has grown over the years and includes the recent elucidation of crystal structure to identify molecular interactions during ligand binding which can aid in designing selective α 2C -adrenoceptor antagonists [35]. Indeed, clinical trials have been performed using α 2C -adrenoceptor antagonists targeting cell surface receptors and include compounds OPC-28326, ORM-12471, and BAY1193397 [36,37]. However, since this receptor is also expressed on the cell surface in non-VSM cells, other tissues, and organs, this approach, although promising in short-term trials, also showed an effect on inhibiting pre-synaptic α 2C -adrenoceptors and in augmenting sympathetic activity over long-term use, which affects heart function [38].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, interest in inhibiting the biological activity of vascular α 2C -adrenoceptors (which play a role as thermo-effectors) has grown over the years and includes the recent elucidation of crystal structure to identify molecular interactions during ligand binding which can aid in designing selective α 2C -adrenoceptor antagonists [35]. Indeed, clinical trials have been performed using α 2C -adrenoceptor antagonists targeting cell surface receptors and include compounds OPC-28326, ORM-12471, and BAY1193397 [36,37]. However, since this receptor is also expressed on the cell surface in non-VSM cells, other tissues, and organs, this approach, although promising in short-term trials, also showed an effect on inhibiting pre-synaptic α 2C -adrenoceptors and in augmenting sympathetic activity over long-term use, which affects heart function [38].…”
Section: Discussionmentioning
confidence: 99%